(untitled) (Research, Society and Development, 2021)
Periapical cysts are formed by the inflammatory process of the epithelium at the apex of non-vital teeth. It usually presents characteristics of slow growth, asymptomatic and of small extension. In this study, the objective is to report a case of periapical cyst with atypical size, submitted to surgical approach. Here, this is a qualitative, descriptive, retrospective study carried out using the technique of direct observation, respecting all ethical protocols. A 74-year-old female patient attended the Buco-maxillofacial Surgery and Traumatology service at Hospital da Restauração Governador Paulo Guerra - Recife, referred by a dentist after analysis of a routine image exam suggestive of a cystic lesion in the mandible. On physical examination, she presented a slight bulging in the vestibular cortex of the right mandibular body, asymptomatic to the touch. Computed tomography revealed a hypodense, unilocular area, circumscribed by a hyperdense line, covering the region of teeth lower lateral incisor, right lower cuspid (canine), right lower firt premolar and right lower second premolar. Based on the clinical examination, the diagnostic hypothesis of periapical cyst was established, confirmed after histopathological analysis. . As a therapeutic approach, it was decided to perform enucleation, peripheral osteotomy and extractions of the teeth involved under general anesthesia. After 8 months of follow-up, she shows no sign of recurrence. Thus, it is clear the importance of correct diagnosis, as well as the efficacy of surgical intervention as a treatment for large periapical lesions.